The Effectiveness of Nusantara Smart Box Media Assisted by Display Advertisements in Learning to Advertise Products to Slow Learners. - Alvina Damayanti; Mintowati (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
The objectives of this study are: 1) to describe the application of Smart Box Nusantara media assisted by pictorial advertisements on the ability to advertise products to 8th grade slow learners at SMPN 24 Surabaya, 2) to describe the effectiveness of Smart Box Nusantara media assisted by pictorial advertisements on the ability to advertise products to 8th grade slow learners at SMPN 24 Surabaya, and 3) to describe the response of 8th grade slow learners at SMPN 24 Surabaya to the use of Smart Box Nusantara media assisted by pictorial advertisements on the ability to advertise products. This type of research uses pre-experimental using a one-group pretest-posttest design. The subjects of this study were 8th grade slow learner students at SMPN 24 Surabaya. Data collection techniques applied observation, tests, and interviews. This study shows the results of observations with a percentage of student activity scores of 91.6% and educator activities of 97.9%. The test results showed an increase in learning outcomes in advertising Indonesian culinary orally with an average pre-test score of 68.2 (KKTPe”82), then experienced an increase in the post-test average of 86.2 (KKTPe”82). Based on the calculation of the Wilcoxon Math Pair Test, it is known that Z count = 2, while Z table = 1.96 (á=5%), so Z count > Z table. The response of slow learner students showed a positive response as evidenced by statements in the interview session.